1999
DOI: 10.1002/(sici)1097-4555(199909)30:9<853::aid-jrs457>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman assays (SERA): measurement of bilirubin and salicylate

Abstract: Results of a study to detect bilirubin and salicylate using SERS and a reactive coating are presented. The motivation for this work was to develop an assay that would simplify an analysis by detecting the analyte in a whole blood sample. This would remove the risks and time associated with preparing a serum sample. Quantitative analysis was performed using partial least-squares. The results are that one can detect bilirubin and salicylate in whole blood at levels below the normal or therapeutic levels using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 21 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Real-time detection of biomolecules using SERS has also been reported ( 111 , 112 ). Yang et al ( 113 ) reported a higher SERS activity of triangular plates due to its sharper corners and edges.…”
Section: Applications Of Anisotropic Nanomaterialsmentioning
confidence: 99%
“…Real-time detection of biomolecules using SERS has also been reported ( 111 , 112 ). Yang et al ( 113 ) reported a higher SERS activity of triangular plates due to its sharper corners and edges.…”
Section: Applications Of Anisotropic Nanomaterialsmentioning
confidence: 99%
“…Their approach required less time and effort than standard processing of whole blood and enabled bilirubin and salicylate (compounds associated with jaundice and poisoning) to be probed within the blood. 221 In 2004, whole blood from scrapie-infected sheep (a fatal, degenerative disease that affects the nervous systems of sheep and goats, related to bovine spongiform encephalopathy, ''mad cow disease'') was collected and processed (subjected to centrifugation and osmotic shock) to produce pellets rich in pathogenic prion proteins. These pellets were analyzed with Raman spectroscopy (1064 nm excitation) and the data from 31 infected sheep were shown to be statistically different than those from 150 healthy controls (no features attributable to b sheet content were present in the controls).…”
Section: Whole Bloodmentioning
confidence: 99%
“…Their approach required less time and effort than standard processing of whole blood and enabled bilirubin and salicylate (compounds associated with jaundice and poisoning) to be probed within the blood. 221…”
Section: Applicationsmentioning
confidence: 99%
“…4,6 More than 1000 articles per year are published detailing various SERS research accomplishments, ranging from single-molecule SERS; medical and cellular interactions; chemical detections; hazard detection; and probably the most prevalent, the manufacture of nanometallic substrate surfaces and colloidal nanoparticles. 7,22…”
Section: Introductionmentioning
confidence: 99%